Optofluidic modification of commercial fiber for passive cooling - Ong, Wei Bin (Nanyang Technological University, 2024)
Developing energy-saving passive cooling method is crucial for achieving COP26’ goal of carbon neutrality and sustainability. Passive radiative cooling in tropical climate (e.g., Singapore, 1.3477N 103.6816E) is challenging due to the high humidity (84% on average), abundant rainfall (~167 days annually), intense solar radiation (up to 1200 W/m2 at daytime with 40% higher UV radiation), and strong downward atmospheric radiation (~20% higher than that of mid-latitude area), which halve the radiative cooling potential; and thus far, there is no report of outdoor daytime sub-ambient radiative cooling under strong solar radiation (power density >1000 W/m2) in tropical climate. In this project, we will investigate the optofluidic modification for passive cooling on commercial fibers in order to make a new fabric with cooling features. Such a fabric would have wide applications from wearables to food storage.